2014
DOI: 10.1074/jbc.m114.568949
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structure and Function of Ciliary and Flagellar Doublet Microtubules

Abstract: Background: Ciliary microtubules contain hyperstable Ribbons of adjoining protofilaments.Results: Using echinoderm flagella, the locations of Ribbons, tektins, and Ca2+-binding proteins (related to human epilepsy) are studied biochemically and by immuno-cryo-electron tomography.Conclusion: The locations of these proteins create a biochemically, structurally unique region of ciliary A-microtubules.Significance: The results indicate specialized functions for Ribbons, with potential roles in assembly, motility, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 90 publications
3
70
1
1
Order By: Relevance
“…As K40 is positioned at the luminal face of MTs, it could potentially regulate the interaction with MT inner proteins (MIPs) (Linck et al, 2014) or MT lattice interactions, and thus MT dynamics. Indeed, in C. elegans touch receptor neurons, the organization of the particular 15-protofilament MTs depends on K40 acetylation (Cueva et al, 2012;Topalidou et al, 2012).…”
Section: Molecular Mechanisms Controlled By Tubulin Ptmsmentioning
confidence: 99%
“…As K40 is positioned at the luminal face of MTs, it could potentially regulate the interaction with MT inner proteins (MIPs) (Linck et al, 2014) or MT lattice interactions, and thus MT dynamics. Indeed, in C. elegans touch receptor neurons, the organization of the particular 15-protofilament MTs depends on K40 acetylation (Cueva et al, 2012;Topalidou et al, 2012).…”
Section: Molecular Mechanisms Controlled By Tubulin Ptmsmentioning
confidence: 99%
“…Labeling techniques that have been combined with cryo-EM imaging include immunogold labeling (15) and, more recently, clonable tags, which have the advantage of higher labeling specificity and resolution (16,17). To avoid disruption of the assembly or architecture of macromolecular complexes, clonable tags are usually designed to be relatively small (e.g.…”
mentioning
confidence: 99%
“…Approximately, 90 % of PCD/KS male patients are affected by AZS and most of them showing dynein genes mutation [16]. It has been demonstrated that tektins participated in the assembly of axonemal microtubules and offered stability to axonemal microtubules [29]. Tektins are a highly conserved family of flagellar and ciliary proteins in many species from invertebrate to higher species, such as Chlamydomonas, sea urchins, zebrafish, hedgehog, rodents, and humans [18,19,28,30,31].…”
Section: Discussionmentioning
confidence: 99%